2020
DOI: 10.1002/dmrr.3233
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy in diabetic foot ulceration: Useless or useful? A battle

Abstract: The use of hyperbaric oxygen therapy (HBO) in the treatment of certain types of diabetic foot ulcers (DFU) has been the topic of much debate and disagreement over the last several decades. In this review, the evidence for its use is presented and discussed by two experts in DFU management. Whereas some randomized controlled trials suggest that HBO may speed the healing of certain ischaemic or neuroischaemic ulcers after the failure of standard of care, most recent trials have been negative. No RCT is perfect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…This is promising, as we have hypothesized, based on the contributing factors for wound healing discussed by Mustoe and collegues discussed 6 . In the literature there is still controversial evidence of hyperbaric medicine in woundcare 28‐33 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is promising, as we have hypothesized, based on the contributing factors for wound healing discussed by Mustoe and collegues discussed 6 . In the literature there is still controversial evidence of hyperbaric medicine in woundcare 28‐33 …”
Section: Discussionmentioning
confidence: 80%
“…With respect to the EQ-5D, 147 to 150 completed questionnaires could be analyzed before and at the end of the wound treatment in the 6 In the literature there is still controversial evidence of hyperbaric medicine in woundcare. [28][29][30][31][32][33] The present study did not make use of a placebo group, and it may be argued that observed changes were due to factors other than hyperbaric oxygen treatment, which is a limitation of the current study. However, the inclusion criteria were chronic wounds that proved to be resistant to healing for a period longer than 3 months despite optimal standard wound care, and as such this functions as a benchmark or control group.…”
Section: Resultsmentioning
confidence: 99%
“…For diabetic foot ulcers (DFU), 30 to 40 treatment sessions of 90 minutes are usually endorsed at pressures between 2.0 and 2.5 ATA in a hyperbaric chamber. 32 Previous high-quality RCTs showed a significant improvement in ulcer healing and decreased amputation rates among DFU patients treated with adjunctive HBOT compared to Standard care of treatment modalities alone. 33 Many preclinical and animal studies have shown that HBO stimulates angiogenesis, reduces oedema, increases the formation of granulation tissue by enhancing fibroblasts, improves leukocyte function, and mobilizes bone marrow stem cells.…”
Section: Revascularisationmentioning
confidence: 95%
“…90 Conclusively, HBOT is considered as an adjunctive treatment for nonhealing ischemic DFUs that do not respond to standard of care. 5,91…”
Section: Adjunct Therapiesmentioning
confidence: 99%